Uji antibakteri ekstrak daun singkong (manihot esculenta crantz) terhadap fusobacterium nucleatum dan aggregatibacter actinomycetemcomitans Antibacterial activity test of cassava leaves extract (manihot esculenta crantz) against fusobacterium nucleatum and aggregatibacter actinomycetemcomitans - Zahara Meilawaty; Amandia Dewi Permana Shita; Rendra Chriestedy Prasetya; Agustin Wulan Suci Dharmayanti; Rido Tri Andika Firdyansyach; Dhea Ayu Dewanti (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2022)
ABSTRAK